All-polarization-maintaining fiber optical frequency comb for the dispersion measurement of a microcavity - Yanyan, Zhang; Pan, Zhang; Mingkun, Li; Jiazheng, Song; Faxi, Chen; Libo, Li; Xuelong, Li; Yuanshan, Liu (Frontiers in Physics, 2022)
In this research, we demonstrate an optical frequency comb (OFC) based on a figure-9 laser and polarization-maintaining fibers to measure the dispersion of integrated micro-resonator. We adopt a multi-branch structure to obtain a broad spectral from 1250 nm to 1640 nm with 6 dB bandwidth. The signal mode power at each wavelength of the supercontinuum spectra is greater than 300 nJ, which assuring the signal-to-noise ratio of the beat notes between the OFC and the diode laser. The frequency stability of repetition rate is about 7.5×10-14 in an integration time of 1 s. This system allows us to extend the measurement bandwidth to 60 THz at sub-megahertz resolution, which meets the requirement of the microcavity’s higher order dispersion measurement.